Government Incentives and Consumer Motives on Electric Vehicle Purchase Intent in Indonesia - Vincentius Christian Laksmana; Putu Anom Mahadwartha (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2024)
Purpose – This research aims to examine how much influence consumer motives have on intentions to purchase licensed electric vehicles. This research also wants to measure the extent of the influence of direct financial incentives on the decision to adopt electric vehicles.Methodology – This research uses 329 valid survey results obtained through distributing online questionnaires. The data was then processed using structural equation modelling to test the empirical similarity of the hypothesis framework.Findings – The results of the structural equation modelling showed that 2 of the 4 independent variables were stated to have a positive impact on purchase intention. Hedonic motives and financial incentives provide the strongest influence on purchase intention.Originality/Novelty – This study is the first in Indonesia to investigate the influence of consumer motives to purchase electric vehicles. This study also evaluates the financial incentives provided by the Indonesian government to accelerate the use of electric vehicles.Implications – The results of this study can help the government formulate public policies that will be designed to increase the use of electric vehicles further.